The Effect of Streptomyces sp. SF5 and Aqueous Extract of Salsola vermiculata on the Growth of Triticum durum L. under Salinity - Ameur, Hanane (Annals of Arid Zone, 2021)
The present study analyzed the effect of NaCl, Salsola vermiculata (halophyte) and Streptomyces sp. SF5 on the growth of MBB variety of durum wheat Triticum durum L. The experiment consisted of twelve treatment combinations carried out in three replications. NaCl solutions (0, 100 and 200 mM) were added to sterile soil with or without aqueous extract of S. vermiculata and Streptomyces sp. alone or in combination. The results showed that this variety was moderately halotolerant. Germination rates at 0, 100 and 200 mM NaCl were 100%, 80% and 53.2% respectively. Combination of S. vermiculata and Streptomyces sp. affected germination rates significantly at different levels of NaCl (46.66%, 40% and 26.6%). Sole application of the halophyte or Streptomyces sp. restored germination to 86.6%, and 93.2% (in 200 mM NaCl) and improved growth of the wheat. Furthermore, the length and the dry weight of roots and stems, chlorophyll a, b and carotenoids contents were also improved significantly. In the presence of 100 and 200 mM NaCl, proline reached levels of 45.3 and 20.31 Î¼g g-1 of fresh material respectively. They were however, reduced in the presence of S. vermiculata and/or Streptomyces sp. SF5.The aqueous extract of S. vermiculata and application of Streptomyces sp. SF5 to a saline soil partially alleviates its adverse effects and improves growth and performance of wheat seedlings.Key words: Salt stress, Triticum durum L., Salsola vermiculata, Streptomyces sp. SF5, plant growth, osmoprotection.